A Morphometric study of superior mesenteric artery and its implication in laparoscopic Surgery - Mane, Rekha Maruti; Shinde, Charushila (International Journal of Medical Research and Review, 2015)
Introduction: As the field of intestinal surgery advanced over the recent century, challenge of performing more complex resection and anastomoses highlighted the presence of vascular variants. The current clinical interest of these anatomic finding is to laparoscopic colon surgeon. Material and method: The study was conducted on a 50 embalmed human cadavers in the Anatomy dissection hall .We performed detailed dissection to measure length and to note a branching pattern of Superior mesenteric artery and its branches. Results: In all 50 cases Superior Mesenteric Artery (SMA) was originated from abdominal aorta, separated from celiac trunk by 0.9cm + 0.29. All five branches were seen in all samples with 2% showed additional branches. A common trunk of Right Colic artery (RCA) and Middle Colic artery (MCA) was noted in 42%. The numbers of Jejuno-Ilel branches were 7-13 in number with most common was 9 (26%). Additional branch from jejunal artery to other viscera was present in 4%. Mean length of MCA, RCA and Ileo-colic was 3.23 + 1.51, 3.42 + 1.17, and 4.57+ 0.98 respectively. Pattern of distribution noted was Type A 58%, Type B 32%, Type C 10%. Conclusion: A normal pattern of colonic vasculature as accepted by most of medical textbook was not seen in all of the cases. The interest in these anatomical concepts was not simply to Anatomist but also to surgeons while performing a safe and efficient laparoscopic or conventional colon surgery.